The Molecular Mechanism of Antioxidation of Huolisu Oral Liquid Based on Serum Analysis and Network Analysis - Yin, Yihui; Zhang, Kai; Wei, Longyin; Chen, Dongling; Chen, Qian; Jiao, Mingjie; Li, Xinxin; Huang, Jiaqi; Gong, Zhexi; Kang, Nianxin; Li, Fei (Frontiers in Pharmacology, 2021)
Huolisu Oral Liquid (HLS) is a widely used traditional Chinese medicine (TCM) compound preparation, which has been widely applied in the clinical treatment of senile diseases and has the effect of delaying aging. The antioxidant effect of HLS is closely related to delaying aging, but the mechanism is unclear. In this study, the potential antioxidant ingredients of HLS were screened based on serum pharmacochemistry and network pharmacology, and the possible mechanism for HLS to exert its antioxidant effect was preliminarily explored, and the antioxidant effect of HLS in vivo and in vitro was verified by experiments. The results showed that potential antioxidant ingredients could affect toxic advanced glycation end-products-the receptor for advanced glycation end-products (TAGE-RAGE) signaling pathway, mitogen-activated protein kinase (MAPK) signaling pathway, interleukin (IL)-17 signaling pathway, tumor necrosis factor (TNF) signaling pathway, Toll-like receptor (TLR) signaling, cyclic adenosine monophosphate (cAMP) signaling pathway, hypoxia-inducible factor (HIF)-1 signaling and other related pathways by regulating GAPDH, AKT1, TP53, MAPK1, JUN and other related targets, through which could reduce inflammation, control the release of inflammatory cytokines, regulate mitochondrial autophagy, metabolic abnormalities, ultimately play an antioxidant role in mice. This is the first time to construct a multi-level network of “HLS-antioxidant targets” based on serum pharmacochemistry and network pharmacology, to explore the relationship between HLS and antioxidation and the molecular mechanism of antioxidation combined with bioinformatics function analysis, which lays a foundation for further elucidating the antioxidant mechanism of HLS.